Serum level of proximal renal tubular epithelial cell-binding immunoglobulin G in patients with lupus nephritis. (January 2016) - Yap, D Y H; Yung, S; Zhang, Q; Tang, C; Chan, T M
In vitro data showed that immunoglobulin G (IgG) from lupus nephritis (LN) patients could bind to proximal renal tubular epithelial cells (PTEC), but the clinical relevance of such binding remained unclear. Binding of IgG and subclasses to PTEC was measured by cellular ELISA (expressed as OD index) in 189 serial serum samples from 23 Class III/IV ± V LN patients who had repeated renal flares (48 during renal flares, 141 during low level disease activity (LLDA)), and compared with 64 patients with non-lupus glomerular diseases (NLGD) and 23 healthy individuals. Total IgG PTEC-binding index was 0.34 ± 0.16, 0.29 ± 0.16, 0.62 ± 0.27 and 0.83 ± 0.38 in healthy controls, NLGD, LN patients during LLDA, and LN patients during nephritic flare, respectively ( p  < 0.001, LLDA vs. renal flare; p  < 0.001, healthy controls or NLGD vs. LN during LLDA or renal flare). PTEC-binding index for IgG1 was 0.09 ± 0.05, 0.16 ± 0.12, 0.44 ± 0.34 and 0.71 ± 0.46 for the corresponding groups ( p  < 0.001, LLDA vs. renal flare; p  < 0.001, healthy controls or NLGD vs. LN during LLDA or renal flare). Sixteen of 48 episodes (33.3%) of nephritic flare showed persistent PTEC-binding IgG seropositivity for more than 9.4 ± 3.1 months, despite clinical response to immunosuppressive treatment. Total IgG and IgG1 PTEC-binding correlated with anti-dsDNA level ( r  = 0.34 and 0.52, respectively, p  < 0.001 for both), and inversely with C3 level ( r  = –0.26 and –0.50, respectively, p  = 0.002 and<0.001). Sensitivity/specificity of PTEC-binding index in detecting renal flares was 45.8%/80.1% for total IgG (ROC AUC 0.630, p  = 0.007) and 87.5%/35.5% for IgG1 (ROC AUC 0.615, p  = 0.018). IgG1 PTEC-binding index correlated with tubulo-interstitial inflammation score in renal biopsy from corresponding patients. Our data suggested that total IgG and IgG1 PTEC-binding index in serum of LN patients correlate with serological activity, and in combination could predict renal flares. The correlation between IgG1 PTEC-binding and tubulo-interstitial inflammation suggests potential pathogenetic significance.